Marine bioinvasions: bivalve molluscs introduced in northeast Brazil - Luan Lucas Cardoso Lima; Flávio Dias Passos (Universidade Estadual de Alagoas, 2021)
ABSTRACT: Invasive alien species are those that, once introduced from other environments, adapt, starting to reproduce and proliferate in places they did not previously inhabit. The introduction of exotic marine species as a result of anthropic activity, whether intentionally or not, is a process that has been remote for centuries, which makes it difficult to assess the impact of these activities, making studies that address the status of knowledge about such organisms always important. Thus, this research aims to gather information about bivalve molluscs introduced into marine ecosystems in northeastern Brazil, in addition to discussing the knowledge of this invasive fauna for the Northeast, Southeast and South regions of Brazil. For that there was a search for bibliography in 5 databases - SciELO, Web of Science, Google Scholar, ScienceResearch.com and I3N Brazil Database of the Horus Institute for Environmental Conservation and Development. Three invasive bivalves for the northeastern region of Brazil were counted. When compared to the South and Southeast regions, the Northeast presents a significant amount of research on the ecology of the species Isognomon bicolor (C. B. Adams, 1845) and Mytilopsis leucophaeata (Conrad, 1831), which is very important, because with these results it is possible to track and understand the pathways that make bioinvasions possible. Regarding Perna Perna (Linnaeus, 1758), although there is a discussion about its supposed introduction in Brazilian waters, the species can be considered invasive in Northeastern Brazil. KEYWORDS: Invasive species, marine ecosystem, ecology.